The millennium development goals (MDGs): gender gap in information, education and library access to HIV/AIDS prevention and treatment in local communities of Nigeria (2007)
The paper discusses Nigerians’ place in the realization of the MDGs as it relates to information, education & library access in rural communities, as a means of halting and reversing the spread of HIV/AIDS among the most vulnerable. It looks at the gender gap in access to information and education about HIV/AIDS prevention and treatment. The rural communities, the poor, the displaced, sex workers, and young women are the most disenfranchised, therefore AIDS consistently moves through these fracture points of society through inequitable gender, social, or economic relations. Radio and television phon- in programmes, indigenous Nigerian language talk shows, community radio transmission and mobile libraries with indigenous multimedia and print materials are empowerment tools useful to demand enhanced services, life saving drugs, basic rights, and air their views, opinions and challenges.